2023
DOI: 10.1021/acs.chemrestox.3c00008
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography–Mass Spectrometry Screening of Cyclophosphamide DNA Damage In Vitro and in Patients Undergoing Chemotherapy Treatment

Abstract: DNA alkylating drugs have been used as frontline medications to treat cancer for decades. Their chemical reaction with DNA leads to the blockage of DNA replication, which impacts cell replication. While this impacts rapidly dividing cancerous cells, this process is not selective and results in highly variable and often severe side effects in patients undergoing alkylating-drug based therapies. The development of biomarkers to identify patients who effectively respond with tolerable toxicities vs patients who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…More recently, Balbo and colleagues introduced an adductomic approach based on high-resolution mass spectrometry . Utilizing this method, DNA adducts formed by the adducting drugs have been examined thoroughly, facilitating the establishment of DNA adduct formation profiles. ,,, With the structural information provided by the mass spectra, specific adducts of interest (e.g., those with high abundance and/or occurrence in multiple individual samples) can be synthesized and quantified . These findings hold promise for the potential use of such adducts as biomarkers to predict the clinical outcome of the adducting drugs.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Balbo and colleagues introduced an adductomic approach based on high-resolution mass spectrometry . Utilizing this method, DNA adducts formed by the adducting drugs have been examined thoroughly, facilitating the establishment of DNA adduct formation profiles. ,,, With the structural information provided by the mass spectra, specific adducts of interest (e.g., those with high abundance and/or occurrence in multiple individual samples) can be synthesized and quantified . These findings hold promise for the potential use of such adducts as biomarkers to predict the clinical outcome of the adducting drugs.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…133 A recent DNA adductomic study identified 40 DNA adducts induced by cyclophosphamide, including known adducts (e.g., Acr-dGuo 133 and 134, N7G-NOR-OH 127, N7G-NOR-Cl 128, and N7G-NOR-N7G 129) and unreported adducts like Acr-dAdo, NOR-FapyG 130, N7G-NOR-FapyG 131. 134 Furthermore, a mass spectrometry-based proteomics approach identified DNA−protein cross-links, including Cys-NOR-N7G 132, in human fibrosarcoma cells (HT1080) treated with the phosphoramide mustard 40. 135 5.1.4.…”
Section: Preclinical Studies Of Dna Adductsmentioning
confidence: 99%